Modifikasi Struktur Jetty Pelat Beton Pracetak Konvensional menjadi Pelat Beton Pracetak Hollow Core Slab - Johannes Tarigan; Emma Patricia Bangun; Indra Fischer (Syntax Corporation Indonesia, 2023)
The wharf is where the ships are moored in the harbour. In addition, the pier is also the place where loading and unloading of goods takes place and passengers boarding and falling from and to the ship. The wharf is also the activity location for refueling ships, supplying ships with drinking water, clean water, and arranging channels for dirty/waste water to be further processed at the port. So that optimum planning is needed so that the performance of the building can meet safety and comfort standards This research modifies conventional precast floor slabs into hollow core slab precast slabs with 2 span variations. Dead loads are calculated based on specific gravity, live loads and traffic loads are calculated by